Diagnostic performance of integrated whole-body 18F-FDG PET/MRI for detecting bone marrow involvement in indolent lymphoma: Comparison with 18F-FDG PET or MRI alone - Chen, Xuetao; Yuan, Tingting; Wei, Maomao; Yu, Boqi; Zhou, Nina; Zhu, Hua; Yang, Zhi; Wang, Xuejuan (Frontiers in Oncology, 2023)
Purpose To investigate the diagnostic performance of integrated whole-body 18F-FDG PET/MRI for detecting bone marrow involvement (BMI) in indolent lymphoma compared with 18F-FDG PET or MRI alone. Methods Patients with treatment-naive indolent lymphoma who underwent integrated whole-body 18F-FDG PET/MRI and bone marrow biopsy (BMB) were prospectively enrolled. Agreement between PET, MRI, PET/MRI, BMB, and the reference standard was assessed using kappa statistics. The sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of each method were calculated. A receiver operating characteristic (ROC) curve was used to determine the area under the curve (AUC). AUCs of PET, MRI, PET/MRI, and BMB were compared using the DeLong test. Results Fifty-five patients (24 males and 31 females; mean age: 51.1 ± 10.1 years) were included in this study. Of these 55 patients, 19 (34.5%) had BMI. Two patients were upstaged as extra bone marrow lesions were detected via PET/MRI. 97.1% (33/34) of participants were confirmed as BMB-negative in the PET-/MRI-group. PET/MRI (parallel test) and BMB showed excellent agreement with the reference standard (k = 0.843, 0.918), whereas PET and MRI showed moderate agreement (k = 0.554, 0.577). The sensitivity, specificity, accuracy, PPV, and NPV for identifying BMI in indolent lymphoma were 52.6%, 97.2%, 81.8%, 90.9%, and 79.5%, respectively, for PET; 63.2%, 91.7%, 81.8%, 80.0%, and 82.5%, respectively, for MRI; 89.5%, 100%, 96.4%, 100%, and 94.7%, respectively, for BMB; and 94.7%, 91.7%, 92.7%, 85.7%, and 97.1%, respectively, for PET/MRI (parallel test). According to ROC analysis, the AUCs of PET, MRI, BMB, and PET/MRI (parallel test) for detecting BMI in indolent lymphomas were 0.749, 0.774, 0.947, and 0.932, respectively. The DeLong test showed significant differences between the AUCs of PET/MRI (parallel test) and those of PET (P = 0.003) and MRI (P = 0.004). Regarding histologic subtypes, the diagnostic performance of PET/MRI for detecting BMI in small lymphocytic lymphoma was lower than that in follicular lymphoma, which was in turn lower than that in marginal zone lymphoma. Conclusion Integrated whole-body 18F-FDG PET/MRI showed excellent sensitivity and accuracy for detecting BMI in indolent lymphoma compared with 18F-FDG PET or MRI alone, demonstrating that 18F-FDG PET/MRI is an optimal method and a reliable alternative to BMB. Trial registration ClinicalTrials.gov (NCT05004961 and NCT05390632)